2018
DOI: 10.1007/s00441-018-2886-y
|View full text |Cite
|
Sign up to set email alerts
|

Reno-protective effects of ursodeoxycholic acid against gentamicin-induced nephrotoxicity through modulation of NF-κB, eNOS and caspase-3 expressions

Abstract: Gentamicin (GNT) is a potent aminoglycoside antibiotic widely used to treat life-threatening bacterial infections. We aim to investigate the potential protective effect of ursodeoxycholic acid (UDCA) against GNT-induced nephrotoxicity. In this study, 24 male Wistar rats were used and randomly divided into four groups of six animals each. Control group received 0.5% carboxymethyl cellulose orally for 15 days, GNT group received GNT 100 mg/kg/day i.p. for 8 days, UDCA group received UDCA orally for 15 consecutiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 98 publications
6
14
0
Order By: Relevance
“…After GS administration, necrotic tubular cells and proteins excreted by tubular cells (Tamm-Horsfall protein) makes tubular cast in that maybe leads to tubular occlusion. In our study similar to other researches administration of different antioxidants reduced tubular cast significantly against GS nephrotoxicity (14,29).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…After GS administration, necrotic tubular cells and proteins excreted by tubular cells (Tamm-Horsfall protein) makes tubular cast in that maybe leads to tubular occlusion. In our study similar to other researches administration of different antioxidants reduced tubular cast significantly against GS nephrotoxicity (14,29).…”
Section: Discussionsupporting
confidence: 92%
“…In our research, serum MDA was increased by GS similar to other reports (27,28). Similar to our study, the other researchers reported improvement of serum MDA against GS nephrotoxicity with administration of different antioxidants (13,17,27,29). The elevated serum MDA shows intensification of free radicals production or lipid peroxidation.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, Sun et al showed that artesunate, an A. annua ingredient, induced apoptosis of lamina propria macrophages and dendritic cells and decreased mucosal expression of TNF-α in a rodent model of colitis [ 83 ]. Numerous studies have associated NF-kB and TNF-α with various inflammatory conditions [ 84 , 85 ]. Therefore, controlling the activation of NF-kB and expression of TNF-α could account for the curative effect of A. annua .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, other observations indicated that GA could mitigate LPO and GSH levels in RIR and NaF nephrotoxicity [41]. NO is a potent vasodilator that physiologically regulates the vascular system and renal tubular function [19,58]. Increased NO level plays the primary role in tissue damage through the reaction with superoxide anion and the production of peroxynitrite as a powerful oxidant.…”
Section: Discussionmentioning
confidence: 99%